Factors for Capacity Building Community Tourism Khlong Luang District Pathumthani Province - et. al., Pinyapat Nakpibal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research were 1) to study factors affecting the development of potential community tourism destinations in Khlong Luang District. Pathum Thani Province. Action research and quantitative research were used and research tools were interview form and questionnaires. Data were collected from in-depth interview, focus group discussion. Qualitative data from 30 key informants was analyzed by using content analysis whereas quantitative data collected from 440 samples (Hair et.al, 2006: 112) Analyze data with basic statistics and structural equations modeling (SEM), The research results were found that Community Attractions in Khlong Luang District Pathum Thani province, including Sufficiency Economy, Sufficiency Economy Learning Center, Lotus Learning Center, Product processing, organic agriculture and community market. Along with factors affecting the development of tourist attractions, tourism communities Khlong Luang District Pathum Thani Province. These include 1) the potential of the community, including the attractions of tourist attractions, facilities and accessibility. 2) Participation consists of finding problems, planning, performing activities Monitoring and evaluation; and 3) The service marketing mix consists of products, prices, distribution channels. Promote marketing, personnel, process, creation and presentation of physical characteristics.